Information Overload: Clarifying the Problem - Zarman, Wendi (Universitas Sebelas Maret, 2021)
This research goal is to clarify three main problems. Firstly, what is the definition of information overload. Secondly, does the abundance of information necessarily cause information overload. Thirdly, to what extent this phenomenon is considered as problem for human being, especially in the current age when internet data grow exponentially. In this case, it is related to the huge amount of electronic data from information technology. For that, library research using qualitative method is applied. Several related works of scientists are examined in order to solve the problem. Result shows that, first, information overload definition is basically the inability of an information recipient to process the excessive information. In human context, this condition brings about negative impact to the recipient. Second, the abundance of information is not the only cause of the problem, but is also related to the attention investment and the capacity of the recipient. Thus, the issue is not merely about the data quantity. Third, information overload is a subjective experience that related to the characteristic of the recipient. It means that some may consider it as a problem, while some other may not.